2022
DOI: 10.1007/s12265-022-10335-9
|View full text |Cite
|
Sign up to set email alerts
|

Learning the Hidden Signature of Fetal Arch Anatomy: a Three-Dimensional Shape Analysis in Suspected Coarctation of the Aorta

Abstract: Neonatal coarctation of the aorta (CoA) is a common congenital heart defect. Its antenatal diagnosis remains challenging, and its pathophysiology is poorly understood. We present a novel statistical shape modeling (SSM) pipeline to study the role and predictive value of arch shape in CoA in utero. Cardiac magnetic resonance imaging (CMR) data of 112 fetuses with suspected CoA was acquired and motion-corrected to three-dimensional volumes. Centerlines from fetal arches were extracted and used to build a statist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…Prior research has shown results consistent with our findings, in which ROC curves were displayed with AUCs ranging from 0.82 to 0.98 16 , the best of which involved technically challenging ultrasound planes, including the sagittal plane of the aortic arch, and were conducted by experts 3,16,23 . Previous studies have centered on constructing diagnostic prediction models based on CoA cases already suspected of having ventricular imbalance and, consequently, undergoing fetal echocardiography in the third trimester 2,3,12,14–18,23,26 . In contrast, the primary objective of this study was to refine the CoA screening procedure to ensure that at‐risk fetuses do indeed undergo the supplementary examinations.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Prior research has shown results consistent with our findings, in which ROC curves were displayed with AUCs ranging from 0.82 to 0.98 16 , the best of which involved technically challenging ultrasound planes, including the sagittal plane of the aortic arch, and were conducted by experts 3,16,23 . Previous studies have centered on constructing diagnostic prediction models based on CoA cases already suspected of having ventricular imbalance and, consequently, undergoing fetal echocardiography in the third trimester 2,3,12,14–18,23,26 . In contrast, the primary objective of this study was to refine the CoA screening procedure to ensure that at‐risk fetuses do indeed undergo the supplementary examinations.…”
Section: Discussionsupporting
confidence: 80%
“…Indeed, a gap exists in the literature concerning AI-assisted screening of less-apparent CHDs, such as CoA, that have lower detection rates. Several previous studies have evaluated manual methods for cardiac biometric measurements to predict CoA, however, they have mainly included third-trimester fetal echocardiography performed owing to a prior suspicion of ventricular disproportion 3,[12][13][14][15][16][17][18] . Furthermore, third-trimester fetal echocardiography, which is often performed at specialized centers, differs from the 18-22-week scan by including additional cardiac planes.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have pointed out that clinical consequences such as hypertension are related to abnormal aortic arch morphology ( 14 ). According to the shape of the aortic arch, it can be defined as gothic, crenel, or romanesque arch, which comes from the corresponding architectural style.…”
Section: Discussionmentioning
confidence: 99%
“…Coarctation of the aorta (CoA) and hypertrophic cardiomyopathy (HCM) are two irrelevant cardiovascular diseases ( 1 ). This report describes a diagnosis, management, and 8-year follow-up in a patient with the co-existence of CoA and HCM.…”
mentioning
confidence: 99%
“…Coarctation of the aorta (CoA) and hypertrophic cardiomyopathy (HCM) are two irrelevant cardiovascular diseases (1). This report describes a diagnosis, management, and Takayasu arteritis (TA) is a chronic granulomatous vasculitis of unknown pathophysiological mechanisms.…”
mentioning
confidence: 99%